Pemanfaatan Bahan Daur Ulang dalam Media Edukasi Anak - Fadilah, Ahmad Arif (Al-DYAS, 2024)
This research discusses the utilization of recycled materials as educational tools for children. The aim was to enhance children's creativity in learning by using discarded items, specifically cardboard, crafted into various artistic forms. Data collection involved observation, interviews, and documentation. The study found that employing recycled materials increased children's creativity in repurposing them into useful items or artworks. Emphasizing the active role of children in the learning process, the use of recycled materials as educational tools successfully improved their ability to generate new ideas and create useful items from discarded materials. For instance, crafting cardboard into an alphabet tree showcased children's creativity.